Creutzfeldt-Jakob Disease: A Decade of Assistential Activity at Centro Hospitalar de Trás-os-Montes e Alto Douro - Marques, Ana João (2024)
Introduction: Sporadic Creutzfeldt-Jakob disease (sCJD) is the most frequent of human prion diseases, with an estimated incidence of 1 case per million / habitants per year. Clinical manifestations include multidomain cognitive impairment with pyramidal, extrapyramidal and/or cerebellar signs. It is a rapidly progressive and fatal disease. Our aim was to do a sociodemographic, clinical and progression evaluation of probable CJD cases diagnosed in Centro Hospitalar de Trás-os-Montes de Alto Douro (CHTMAD) since 2010. Methods: Retrospective, descriptive study based on clinical records of all probable CJD cases diagnosed, consecutively included, between January 2010 and July 2020. Results: We identified 13 cases of probable DCJ (6 women). Median age at beginning of symptoms was 68 years (44-74). The most common form of presentation was cognitive impairment (46.2%), followed by myoclonus (38.5%), ataxia (23.1%), pyramidal signs (23.1%) and extrapyramidal signs (23.1%). In about 3⁄4 of patients there was an initial period of unspecified symptom such as strange behavior, anorexia, insomnia and dizziness. Neurological observation occurred at a median of 30 days after symptoms installation (15-240). Brain magnetic resonance imaging showed cortical hypersignal (T2/T2FLAIR or diffusion-weighted) in 84.6% of patients and basal ganglia hypersignal in 61.5%. Most frequent electroencephalogram anomaly was the presence of periodic discharges/complexes (46.2%). Cerebrospinal fluid analysis was positive for 14.3.3 protein in all cases. Median survival was 3 months (2-13). Autopsy was authorized in only 5 patients, confirming the diagnosis. Conclusion: Our group of patients illustrate phenotypic variability of CJD and brings attention to the existence of an initial phase of unspecified symptoms, when prompt investigation may allow earlier diagnosis.